BOAS PRÁTICAS DE ATENÇÃO AO PARTO E NASCIMENTO: DESENVOLVIMENTO, VALIDAÇÃO E IMPLEMENTAÇÃO DE UM INSTRUMENTO DE AUTOAVALIAÇÃO PROFISSIONAL COM BASE NAS RECOMENDAÇÕES DA ORGANIZAÇÃO MUNDIAL DA SAÚDE - Fenner, Paola Carvalho (2019)
Introduction: The most recent national government policies aiming to qualify care for childbirth and birth at the national level are in line with the recommendations of the World Health Organization, proposed in 1996 through a guide that provides good care practices for childbirth and birth. Still, proposals that involve health education become necessary in hospital institutions, when studies have pointed out that assistance that is too interventional, impersonal and without scientific support, remains present in the Brazilian reality. The research, proposed in this dissertation, adds to the studies and actions that have become more frequent in Brazil in the last four decades and intends to contribute at the municipal level to the strengthening of a new model of hospital care for the pregnant, parturient and puerpera women, their baby and his family. It is the proposition of a management strategy that innovates, suggesting the professional self-evaluation and the construction of collective spaces for the fracturing of fragilities identified in a hospital obstetric unit. General objective: To develop, validate and implement a professional self-assessment tool, together with hospital birth attendance professionals, in order to enhance good practices in childbirth and birth care. Method: It was a methodological and descriptive research, with a qualitative and quantitative approach, focusing on the construction, validation and application of an instrument. Participated eight expert judges who evaluated the instrument and as 36 professionals who work in the care of childbirth and birth, in addition to one hundred puerperas attended by these same professionals. Results: This dissertation gave rise to instrument of professional self-evaluation for the performance of care in childbirth and delivery was composed of 75 questions based on 25 recommendations of the World Health Organization regarding practices considered to be useful and should be encouraged. It was evaluated by eight judges who considered that 34 were unclear or confused, with suggestions for adequacy. These questions were reformulated, based on the suggestions made by the judges and, after adjustments, the instrument was applied to the professionals who make up a hospital birth assistance team. The perception of health professionals is that the recommendations of the World Health Organization are predominantly attended by the team in which they work, with agreement above 80% in 11 of the 25 recommendations evaluated. Likewise, the perception of puerperae is predominantly positive regarding the care received at the time of the birth of their babies. Final considerations: The creation of spaces for dialogue and discussion of professional practices, together with the evaluation of the users of the service regarding the assistance received, allows to strengthen the reflections and encourage the use of effective strategies for care. Product of the dissertation: It is as product of the dissertation an Instrument for Professional Self-Assessment about Good Practices of Assistance to the Birth that was developed, validated and implemented in a hospital obstetric unit. After the defense of the dissertation, the instrument will remain available to the team where the research was developed and will also be sent to the Sofia Feldman Hospital of Belo Horizonte, an institution that participated in this research indicating the judges who validated it.